Picture-Based Poetry Writing Book To Develop Poetry Writing Skills For Elementary School Students - Lintyasari, Gentry Dhena; Widosari, Ani; Juhana, Juhana (Institut Agama Islam Negeri Palopo, 2022)
This study aims to develop a product in the form of a poetry writing book with the help of image media. This research is a Research and Development research using the Borg and Gall design. This research was conducted in the Rembang sub-district using a sample of four elementary schools. The products developed will be tested for quality and feasibility based on their validity, practicality, and effectiveness. Data was collected using observations, interviews, and writing skills tests. After the data is collected, the data will be analyzed using descriptive qualitative techniques to analyze qualitative data and statistical analysis techniques to analyze quantitative data. The mean obtained from the statistical analysis was converted into a qualitative value. The results showed that the product in the form of teaching materials for writing poetry with the aid of picture media obtained valid, practical, and effective categories for use in learning.